2005
DOI: 10.1159/000084683
|View full text |Cite
|
Sign up to set email alerts
|

Height, Weight, IGF-I, IGFBP-3 and Thyroid Functions in Prepubertal Children with Attention Deficit Hyperactivity Disorder: Effect of Methylphenidate Treatment

Abstract: Objective: To investigate if there are any disease-related or methylphenidate-induced aberrations in growth parameters, growth hormone insulin-like growth factor (IGF)-I, IGFBP-3 axis and the thyroid function tests in children with attention deficit hyperactivity disorder (ADHD). Methods: Newly diagnosed and untreated prepubertal children with ADHD were longitudinally followed before and approximately every 4 months after methylphenidate treatment for up to 16 months. Height SDS, weight SDS, BMI SDS, serum GH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 45 publications
3
39
0
2
Order By: Relevance
“…14 In contrast, among stimulantnaive patients with ADHD, baseline height may be slightly greater than population norms, 9 and children referred for ADHD treatment are reportedly taller at baseline than those not referred. 9,15,16 The Multimodal Treatment Study of Children With ADHD Cooperative Group reported that untreated prepubertal children with ADHD had average height Z scores that increased over time, suggesting faster growth than population norms. 17 More research is needed to assess associations between ADHD and dysregulated growth.…”
Section: Discussionmentioning
confidence: 99%
“…14 In contrast, among stimulantnaive patients with ADHD, baseline height may be slightly greater than population norms, 9 and children referred for ADHD treatment are reportedly taller at baseline than those not referred. 9,15,16 The Multimodal Treatment Study of Children With ADHD Cooperative Group reported that untreated prepubertal children with ADHD had average height Z scores that increased over time, suggesting faster growth than population norms. 17 More research is needed to assess associations between ADHD and dysregulated growth.…”
Section: Discussionmentioning
confidence: 99%
“…retardation, possible tolerance to growth inhibition over time, and then rebound growth. 2,4,[24][25][26][27][28] Temporary growth retardation related to stimulant therapy may partly explain altered growth trajectories among children with ADHD, but alternate hypotheses may also implicate the pathophysiology of ADHD. 25 Although direct evidence is generally lacking, 4 several hypotheses have been considered.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, older results on the effect of stimulant medication on GH secretion appear to be somewhat contradictory. Indications from a number of laboratories are that stimulant usage can cause a decrease in GH secretory activity [37][38][39][40], as well as a decrease in IGF levels [2,41]. A case study by Barter and Krammer [38] showed that methylphenidate is associated with suppression of sleep-induced GH release, while a case study by Holtkamp et al [37] found a decrease in GH secretion in a child experiencing almost complete growth arrest following methylphenidate intake.…”
Section: Stimulants and Growth Hormonementioning
confidence: 99%
“…In order to determine whether a relationship exists between stimulant intake and growth in children with ADHD, the first question to be asked is how un-medicated children with ADHD compare in size to control subjects. Although some studies found un-medicated children with ADHD to be of normal height [1][2][3], weight [1,2] and body mass index (BMI) [2,4]; several, in fact the majority, of studies indicated that un-medicated children with ADHD are actually taller [5][6][7][8][9] and heavier than normal [3,[5][6][7][8]10]. These findings, therefore, contradict the initial suggestion [11] that height deficits in ADHD may be mediated by the disease itself.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation